British White Trash : Figurations of Tainted Whiteness in the Novels of Irvine Welsh, Niall Griffiths and John King /: Figurations of Tainted Whiteness in the Novels of Irvine Welsh, Niall Griffiths and John King. (2018) - Schmitt, Mark
No abstract available